TRANSLATION METHODS AND ITS QUALITY IN MUNIBA MAZARI’S “WE ALL ARE PERFECTLY IMPERFECT” SPEECH TRANSLATION - Putri Zhafirah Ansar; Zuhron Zuhron (Asosiasi dosen IDEBAHASA KEPRI, 2022)
This research examined the classification of translation method of Newmark (1988) used by the translator in translating “We All Are Perfectly Imperfect” speech by Muniba Mazari (2018) and the translation quality assessment by referring to Nababan’s theory. This research used descriptive qualitative word. The data were collected through documentation, because the data were taken from Muniba Mazari’s “We All Are Perfectly Imperfect” speech translation by Paja Tapuih (in form of article). The result of this research indicate that six out of eight translation methods were applied in this research with Literal Translation as the most dominant method used. There are 277 data with Literal Translation method, 48 data with Communicative Translation method, 31 data with Faithful Translation method, 29 data with Word for Word Translation method, 10 data with Semantic Translation method, and 6 data with Free Translation method. Besides, the researcher also assess the quality of its translation with the methods used by the translator which refers to this three aspects, namely aspects of accuracy, aspects of acceptability and aspects of readability.